Analisis Penerapan Customized Business Model untuk Meningkatkan Daya Saing di Sektor Wedding Organizer - ANDANY, ARASIMA (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
This study analyzes the implementation of a customization business model with four approaches (collaborative, adaptive, cosmetic, and transparent) and marketing strategies at Pangestu Organizer, a wedding and event organizer service business in Kediri City. Qualitative research methods were used with data collection through observation, interviews, and documentation. Pangestu Organizer implements a marketing strategy that focuses on personalized approach and participating in fairs to increase visibility. The four customization approaches contribute to positive client experience and company reputation. Service quality is maintained through the implementation of strict Standard Operating Procedures (SOPs), which support high levels of client satisfaction.Keywords: customization business model, marketing strategy, service quality, client satisfaction, wedding and event organizer, Pangestu Organizer.